Revising the revolution : the unmaking of Russia's official history of 1917 - Holmes, Larry E. (Larry Eugene), 1942- (Indiana University Press, 2021)
"The clash between scholarship and politics-between truth and propaganda-was ruthless for historians in Istpart, the Russian Communist Central Committee's official historical department. As part of the state publishing house, Istpart was tasked with preserving the documentary record, compiling memoirs, and upholding ideological conformism within the national narrative of the 1917 revolution. In Revising the Revolution, Larry E. Holmes examines the role of Ispart's historians, both in the Moscow office and a regional branch in Viatka, who initially believed they could adhere to the traditional standards of research and simultaneously provide a history useful to the party. However, they quickly realized that the party rejected any version of history that suggested nonideological or nonpolitical sources of truth. By 1928, Istpart had largely abandoned its mission to promote scholarly work on the 1917 revolution and instead advanced the party's master narrative. Revising the Revolution explores the battle for the Russian national narrative and the ways in which history can be used to centralize power"--